(untitled) (Research, Society and Development, 2022)
The objective was to study the imbibition curves of the seeds in order to determine if the seed coat works as a barrier to the absorption of water, impairing the germination process. The experimental design used was a completely randomized design, conducted with four replications of 25 seeds taken from mature fruits of five Passifloras species, P. edulis f. flavicarpa, P. edulis Sims, P. alata Curtis, P. alata spp, P. mucronata Lam. Two treatments were used: T0 whole seed T1 seed with incised seed coat on the side. The seeds were weighed before immersion in water, and then at one-hour intervals until the first 09 hours, after every 24 hours, ending with 240 hours of analysis. Results were expressed in percentages. In the incised seeds, it was observed that the water gain occurred more quickly in the first hours, and these seeds had an average increase from 18.8 to 37.5% when compared to the beginning of the imbibition process and in the whole seeds of 12.2 to 26.7%. Passifloras seeds follow the three-phase pattern of water absorption, with phase I between zero and 20 hours, phase II between 20 and 180 hours and phase III was observed only in P. edulis Sims at 220 hours. It is concluded that the germination speed of the seeds is positively influenced by the incision, evidencing its physiological dormancy.